2022
DOI: 10.3390/nu14071363
|View full text |Cite
|
Sign up to set email alerts
|

Food-Specific Inhibition Training for Food Devaluation: A Meta-Analysis

Abstract: Theories have suggested that food-specific inhibition training could lead to food devaluation which, in turn, may help people to regulate their eating behavior. In this review, we have synthesized the current literature on this topic by conducting a meta-analysis of studies investigating the effects of food-specific inhibition training on food evaluation. We identified 24 studies—with 36 independent samples, 77 effect sizes, and 3032 participants—that met our inclusion criteria. Effect sizes were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 74 publications
(146 reference statements)
0
19
0
Order By: Relevance
“…As before, this expectation was confirmed for explicit, but not for implicit meat disgust, from simple bivariate correlations of change scores. This may be because implicit attitudes tend to change on different time scales (51)(52)(53)(54), or because our study was not powerful enough to detect a smaller effect, as our post-hoc power analysis suggests. The effect on explicit meat disgust was further confirmed in a regression model predicting changes in this variable: changes in meat intake during Veganuary were most predictive of changes in meat disgust in the expected direction-the more people reduced their meat intake relative to their baseline meat intake, the more their feelings of disgust toward meat grew.…”
Section: Discussionmentioning
confidence: 85%
“…As before, this expectation was confirmed for explicit, but not for implicit meat disgust, from simple bivariate correlations of change scores. This may be because implicit attitudes tend to change on different time scales (51)(52)(53)(54), or because our study was not powerful enough to detect a smaller effect, as our post-hoc power analysis suggests. The effect on explicit meat disgust was further confirmed in a regression model predicting changes in this variable: changes in meat intake during Veganuary were most predictive of changes in meat disgust in the expected direction-the more people reduced their meat intake relative to their baseline meat intake, the more their feelings of disgust toward meat grew.…”
Section: Discussionmentioning
confidence: 85%
“…An a priori sample size calculation indicated that 64 (i.e., 32 per group) participants would be minimally sufficient to detect a small to medium effect size of d = .25 based on a within‐between interaction between 3 measurements and 2 groups, a power of 80%, an alpha of 5%, and an intraclass correlation of 70% (Cohen, 1988; Faul et al, 2007). The proposed effect size was extracted from a recent meta‐analysis of controlled studies utilizing the food‐specific Go/No‐Go training paradigm to reduce food evaluations (Yang et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Although measured in myriad ways, pertinent methods that have been used in previous empirical studies include quicker attentional shift and fixation on a food stimulus (i.e., attentional bias; Field et al, 2016), preference for immediate over delayed food reward (Amlung et al, 2016), and a faster reaction time to select or approach a given food stimulus (Veling et al, 2021). Although cognitive bias modification techniques designed to address these biases have demonstrated efficacy in altering dietary behaviours, primarily in short‐term laboratory settings, the evidence underpinning response inhibition training (RIT) has emerged as the most consistently promising (Allom et al, 2016; Aulbach et al, 2019; Jones et al, 2016; Turton et al, 2016; Yang et al, 2022). RIT ostensibly addresses deficits in inhibitory control upon exposure to energy‐dense, palatable food cues associated with a high reward value (Hofmann et al, 2008; Verbruggen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, repeatedly not responding to a food may lead to the formation of stimulus-stop associations [7], which can automatically suppress the action tendency triggered by the food. Second, not responding to a food can reduce its reward value [8]. This devaluation effect may arise from the hardwired link between inhibition and the aversive system [9,10].…”
Section: Introductionmentioning
confidence: 99%